Cocaine war - Augeropoulos, Yorgos ([S.l.] : Journeyman Pictures, 2004)
This video discusses about the effort against cocaine in Columbia
Executive produces, Anastasia Skoubri
Narrator: Clive Aldiss
Keywords: Cocaine; Drug control -- Corrupt practices -- Columbia